An oligopeptide/aptamer-conjugated dendrimer-based nanocarrier for dual-targeting delivery to bone. Issue 12 (11th March 2021) - Ren, Mingxing; Li, Yuzhou; Zhang, He; Li, Lingjie; He, Ping; Ji, Ping; Yang, Sheng
Abstract : The CH6-PAMAM-C11 dual-targeting nanocarrier can better deliver drugs to sites of osteoblast activity in vivo . Abstract : Bone targeting is one of the most potentially valuable therapeutic methods for medically treating bone diseases, such as osteoarthritis, osteoporosis, nonunion bone defects, bone cancer, and myeloma-related bone disease, but its efficacy remains a challenge due to unfavorable bone biodistribution, off-target effects, and the lack of cell specificity. To address these problems, we synthesized a new dual-targeting nanocarrier for delivery to bone by covalently modifying the G4.0 PAMAM dendrimer with the C11 peptide and the CH6 aptamer (CH6-PAMAM-C11). The molecular structure was confirmed using 1 H-NMR and FT-IR spectroscopy. CLSM results showed that the novel nanocarrier could successfully accumulate in the targeted cells, mineralized areas and tissues. DLS and TEM demonstrated that CH6-PAMAM-C11 was approximately 40–50 nm in diameter. In vitro targeting experiments confirmed that the C11 ligand had a high affinity for HAP, while the CH6 aptamer had a high affinity for osteoblasts. The in vivo biodistribution analysis showed that CH6-PAMAM-C11 could rapidly accumulate in bone within 4 h and 12 h and then deliver drugs to sites of osteoblast activity. The components of CH6-PAMAM-C11 were well excreted via the kidneys. The accumulation of many more CH6-PAMAM-C11 dual-targeting nanocarriers than single-targeting nanocarriers was observed in the periosteal layer of the rat skull, along with aggregation at sites of osteoblast activity. All of these results indicate that CH6-PAMAM-C11 may be a promising nanocarrier for the delivery of drugs to bone, particularly for the treatment of osteoporosis, and our research strategy may serve as a reference for research in targeted drug, small molecule drug and nucleic acid delivery.